(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The LRBG operation in the correction of DLP in patients with MS is limited in application. In order to correct disorders in the lipid spectrum, the operation is advisable to use only in young age groups, among women, with an initial BMI of no more than 43 kg / m2, not "sweet tooth", capable of following all the recommendations of the attending physician for a long period of time. The use of this type of operation in men is not advisable, since the effectiveness of the operation, after a year of observation, returns to the original data, while their quality of life is significantly reduced.